Challenges Faced by EFL Teachers in Setting Learning Objectives for Writing Materials in the Senior High School Context - Hasriani G; Nurmaisyah Nurmaisyah; Sahril Nur (English Education Department, 2025)
This study investigates the challenges encountered by English as a Foreign Language EFL teachers in setting learning objectives for writing instruction in Indonesian senior high schools Using a qualitative phenomenological design data were collected through questionnaires and semi structured interviews with 20 EFL teachers across various schools in Makassar followed by thematic analysis to identify shared patterns of experience The findings reveal five major themes: challenges in curriculum interpretation constraints from student related factors instructional design limitations adaptive strategies for objective setting and institutional and professional needs Teachers reported difficulty translating the broad competencies of nbsp;< span>Kurikulum 2013< em> nbsp;< span>into measurable classroom objectives due to limited training in curriculum interpretation and instructional design They also faced learner heterogeneity low motivation and writing anxiety which necessitated process based and differentiated goals Despite these barriers teachers demonstrated pedagogical agency through adaptive strategies such as backward design pre assessment authentic writing tasks and technology assisted feedback to enhance coherence and engagement The study highlights the need for sustained practical and context specific professional development that connects curriculum theory with classroom practice Institutional mentoring and professional learning communities are recommended to strengthen teachers ability to design realistic measurable and contextually relevant objectives for EFL writing instruction The research contributes to the broader understanding of teacher cognition and curriculum enactment illustrating how educational policy pedagogical decision making and local realities interact to shape the quality of writing instruction in Indonesia < span>< div>